Preperation of KGB agent for intelligence task and evaluation of their activity - Burinskaitė, Kristina (Genocidas ir rezistencija, 2018)
The activities of KGB agents are still of great public interest. People are particularly concerned about the names behind the aliases of those who agreed to cooperate with the Soviet security services. They are less interested in the circumstances under which these individuals became KGB agents, the objectives and functions they were supposed to fulfil and what they actually did. The level of cooperation with the KGB varied: some worked enthusiastically, out of ideological motives, others only under duress. The actual activities of agents determine the extent of their liability. Of course, the mere fact of agreeing to cooperate with the KGB does not contribute positively to the biography, because it is a personal choice. So behind the aliases are extraordinary stories of people.
Keywords: Lithuania; KGB; agents; intelligence; West